Filter membrane prepared based on electrostatic spinning-fog polymerization synergy and preparation method thereof

Through the collaborative preparation technology of electrospinning and mist polymerization, an efficient antibacterial nanofiber filter membrane was prepared, which solved the problems of poor filtration efficiency and insufficient antibacterial performance of traditional materials under high air flow, and achieved efficient filtration and antibacterial effects to ensure the health of workers.

CN120242759AActive Publication Date: 2025-07-04SHANDONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510374069.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-07-04
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

Traditional protective materials have poor filtration efficiency under high air flow and do not have antibacterial properties, which cannot effectively prevent bacteria from reproduction on the filter membrane, resulting in increased health risks.

Method used

The collaborative preparation technology of electrospinning and mist polymerization is adopted to form nanofiber membranes through electrospinning, and antibacterial modification is performed using the atomization treatment of initiators and solvents to prepare a highly efficient antibacterial nanofiber filter membrane.

Benefits of technology

Maintain high filtration efficiency and antibacterial effect under high air flow, reduce bacterial reproduction risks, improve wear comfort, and reduce respiratory system damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120242759A_ABST
    Figure CN120242759A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a filter membrane based on electrostatic spinning-fog polymerization synergy, which comprises the following steps: dissolving a high-molecular polymer raw material capable of polymerizing to form fibers in N, N-dimethylformamide, adding methacrylic acid, and stirring to obtain a spinning solution; performing electrostatic spinning and vacuum drying to form a nanofiber membrane; and finally, immersing the nanofiber membrane into an initiator, carrying out atomization treatment in a DMC-containing or DMC-free solvent, washing, and drying to obtain a finished product of the filter membrane. The prepared filter membrane is excellent in performance, high in filtering efficiency and reasonable in pressure drop under different air flow rates, for example, when the air flow rate is 85 L / min, the filtering efficiency is 90.44%-96.76%, and the pressure drop is 124.5 Pa-211.7 Pa; the bacteriostasis rate on escherichia coli reaches up to 86.3%; the hydrophilicity is good, and the minimum contact angle is 9.7 degrees. The preparation method is simple and convenient to operate, easy in process parameter regulation and control and environment-friendly, provides a new choice for personal protection equipment materials, and effectively solves the problem of air pollution protection in operation environments such as mines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and particularly to a filter membrane prepared by electrospinning-fog polymerization synergy and a preparation method thereof. Background Art

[0002] With the acceleration of the industrialization pace, the air pollution problem in the mine production environment has gradually intensified. Especially, the concentration of particulate matter (PM) has been continuously rising, posing a serious threat to human health. Long-term exposure to a high-concentration PM polluted environment makes people prone to suffer from diseases such as respiratory system diseases, and may even cause cancer. In the mine operation environment, although a series of measures such as coal seam water injection, ventilation and air change, and spray dust reduction have been taken to improve the underground operation conditions, the concentration of respirable dust still far exceeds the national standard. In addition, the underground mine environment is humid, hot and dusty. During long-term high-intensity labor, breathing will generate hot air and water vapor, which all provide favorable conditions for the growth of bacteria. The reproduction of bacteria in the filter medium will not only reduce the filtration efficiency, but also may cause health problems such as respiratory tract infections.

[0003] Traditional protective materials such as cotton, non-woven fabric, melt-blown fiber, etc., although can block particulate matter in the air to a certain extent, but in the case of high air flow rate (such as 85 L / min), there is still a large room for improvement in their filtration efficiency and antibacterial properties. Taking melt-blown fiber as an example, under the impact of high-flow air, some fine particulate matters are easy to penetrate through the fiber gaps, resulting in poor filtration effect; moreover, traditional materials themselves do not have antibacterial functions and cannot inhibit the growth and reproduction of bacteria on their surfaces. Therefore, it is urgent to develop a personal protective equipment material with high antibacterial efficiency and still maintaining good filtration performance under high air flow rate. Summary of the Invention

[0004] The present invention provides a method for preparing a filter membrane by electrospinning-fog polymerization synergy, comprising the following steps:

[0005] S1. Dissolve a polymer raw material that can polymerize to form fibers in N,N-dimethylformamide, stir evenly to obtain a spinning solution with a predetermined concentration, and then add a modifier and continuously stir until uniform;

[0006] S2. Load the stirred precursor solution into a syringe, perform electrospinning at a set injection rate and voltage, and then vacuum dry to form a nanofiber membrane;

[0007] S3. Immerse the nanofiber membrane in an initiator, heat to 60 °C to decompose the initiator to generate free radicals, pour a solvent containing or not containing DMC into an atomization cup, keep the surface of the fiber membrane 8 cm away from the atomization nozzle for atomization, after the spraying is finished, dry the fiber membrane, place the dried nanofiber membrane in distilled water for washing, and finally dry to obtain a finished nanofiber membrane.

[0008] Preferably, in S1, continuously stir at 60 °C for 3 h until the solution becomes uniform in texture to obtain a 10 wt% spinning solution, and the amount of the modifier added is 0.5 g or 1 g.

[0009] Preferably, in S2, inject at a controllable feeding rate of 1.2 ml / h, and perform electrospinning under a high voltage of 18 kV. The rotating roller rotates at a speed of 200 r / min, and the spinning duration is 40 min.

[0010] Preferably, the conditions for vacuum drying are: vacuum drying at 25 °C for 2 hours.

[0011] Preferably, the atomization time in S3 is 5 min. After the spraying is completed, place the fiber membrane in an oven at 80 °C for 10 min. Wash the dried nanofiber membrane three times with 50 mL of distilled water for 5 min each time, and then dry it in an oven at 80 °C for 30 min.

[0012] Preferably, the concentration of DMC is 0.5% - 5%.

[0013] Preferably, the polymer raw material that can be polymerized to form fibers is one of polyacrylonitrile, polyethylene glycol, or polyethylene oxide, and the modifier is selected as methacrylic acid.

[0014] In addition, the present invention also provides a filter membrane prepared by the synergistic preparation of electrospinning - mist polymerization, which is prepared by the method described above.

[0015] Preferably, when the air flow rate is 32 L / min, the filtration efficiency of the filter membrane is 96.54% - 99.91%, and the pressure drop is between 22.7 Pa and 34.6 Pa;

[0016] When the air flow rate is 65 L / min, the filtration efficiency is 92.39% - 98.63%, and the pressure drop is between 77.6 Pa and 82.8 Pa;

[0017] When the air flow rate is 85 L / min, the filtration efficiency is between 90.44% and 96.76%, and the minimum pressure drop is 124.5 Pa and the maximum is 211.7 Pa

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0019] (1) The present invention adopts electrospinning technology and "mist polymerization" technology, which is simple to operate, easy to control process parameters, and environmentally friendly. The fiber filter membrane prepared by these two technologies has a fiber diameter that can reach the nanoscale and is uniform in diameter, laying a solid foundation for the realization of excellent performance of the filter membrane.

[0020] (2) The antibacterial rate of the nanofiber filter membrane prepared by the present invention against Escherichia coli is as high as 86.3%, showing good antibacterial effects. This property effectively reduces the risk of bacteria breeding and multiplying on the filter membrane, greatly reduces the possibility of health problems such as respiratory infections caused by bacterial transmission, and effectively protects the physical health of workers.

[0021] (3) The nanofiber filter membrane prepared by the invention has a filtration efficiency of 96.76% and a minimum pressure drop of 124.5 Pa at a test flow rate of 85 L / min. While effectively blocking airborne particulate matter, this filter membrane can ensure smooth breathing for workers, providing reliable personal protection and effectively reducing the damage to the respiratory system caused by inhaling dust. At the same time, the nanofiber filter membrane has excellent hydrophilic properties, with a minimum contact angle of up to 9.7°. The lower contact angle indicates that the filter membrane has excellent hydrophilicity, can quickly absorb the water vapor generated by workers' breathing, avoid the accumulation of water vapor on the surface of the filter membrane, significantly improve the wearing comfort, reduce the discomfort caused by dampness and heat, and make workers more comfortable and convenient during long-term operations. Description of the Drawings

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0023] Figure 1 It is the process flow chart of preparing the nanofiber membrane by electrospinning of the present invention;

[0024] Figure 2 It is a schematic diagram of the filtration efficiency and filtration pressure drop of the nanofiber membrane in each embodiment at a test flow rate of 32 L / min;

[0025] Figure 3 It is a schematic diagram of the filtration efficiency and filtration pressure drop of the nanofiber membrane in each embodiment at a test flow rate of 65 L / min;

[0026] Figure 4 It is a schematic diagram of the filtration efficiency and filtration pressure drop of the nanofiber membrane in each embodiment at a test flow rate of 85 L / min;

[0027] Figure 5 It is a schematic diagram of the analysis of the anti-Escherichia coli performance of the nanofiber membrane;

[0028] Figure 6 It is a schematic diagram of the test results of the contact angle of the nanofiber membrane in each embodiment. Detailed Embodiments

[0029] The embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. It should be noted that, without conflict, the following embodiments and the features in the embodiments may be combined with each other; and, based on the embodiments in the present disclosure, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present disclosure.

[0030] The following describes various aspects of embodiments within the scope of the appended claims. It should be apparent that the aspects described herein can be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, those skilled in the art should understand that one aspect described herein can be implemented independently of any other aspect, and two or more of these aspects can be combined in various ways. For example, any number of aspects described herein can be used to implement a device and / or practice a method. Additionally, this device can be implemented and this method can be practiced using other structures and / or functionality in addition to one or more of the aspects described herein.

[0031] Unless otherwise specified, the materials in the embodiments are prepared according to existing methods or directly purchased from the market.

[0032] Example 1

[0033] Preparation of the spinning solution: Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF), and continuously stirred at 60 °C for 3 h until the solution was homogeneous in texture, obtaining a 10 wt% spinning solution. 0.5 g of methacrylic acid (MAA) was added to the well-stirred spinning solution, and continuously stirred until homogeneous;

[0034] Preparation of electrospun fibers: The well-stirred precursor solution was loaded into a syringe and injected at a controllable feeding rate of 1.2 ml / h, and electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm, and electrospinning was carried out for 40 min, and vacuum dried at 25 °C for 2 h;

[0035] Antibacterial modification of electrospun fibers: The nanofiber membrane was immersed in the initiator azobisisobutyronitrile (AIBN), heated to 60 °C, and AIBN decomposed to generate free radicals. 5 mL of the solvent without DMC was poured into the atomizing cup, the surface of the fiber membrane was kept 8 cm from the atomizing nozzle, and atomizing operation was carried out for 5 min. After spraying, the fiber membrane was placed in an oven at 80 °C for 10 min. The modified nanofiber membrane was placed in 50 mL of distilled water and washed three times, 5 min each time, and then dried in an oven at 80 °C for 30 min to obtain the nanofiber membrane sample #1.

[0036] Example 2

[0037] Preparation of spinning solution: Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF), and continuously stirred at 60 °C for 3 h until the solution was homogeneous, obtaining a 10 wt% spinning solution. 0.5 g of methacrylic acid (MAA) was added to the well-stirred spinning solution and continuously stirred until homogeneous;

[0038] Preparation of electrospun fibers: The well-stirred precursor solution was loaded into a syringe and injected at a controllable feeding rate of 1.2 ml / h, and electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm. Electrospinning was carried out for 40 min and vacuum dried at 25 °C for 2 h;

[0039] Antibacterial modification of electrospun fibers: The nanofiber membrane was immersed in the initiator azobisisobutyronitrile (AIBN), heated to 60 °C, and AIBN decomposed to generate free radicals. 5 mL of a 1% DMC solution was poured into the atomization cup, and the surface of the fiber membrane was kept 8 cm away from the atomization nozzle for atomization operation for 5 min. After spraying, the fiber membrane was placed in an oven at 80 °C for 10 min. The modified nanofiber membrane was placed in 50 mL of distilled water and washed three times, 5 min each time, and then dried in an oven at 80 °C for 30 min to obtain nanofiber membrane sample #2.

[0040] Example 3

[0041] Preparation of spinning solution: Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF), and continuously stirred at 60 °C for 3 h until the solution was homogeneous, obtaining a 10 wt% spinning solution. 0.5 g of methacrylic acid (MAA) was added to the well-stirred spinning solution and continuously stirred until homogeneous;

[0042] Preparation of electrospun fibers: The well-stirred precursor solution was loaded into a syringe and injected at a controllable feeding rate of 1.2 ml / h, and electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm. Electrospinning was carried out for 40 min and vacuum dried at 25 °C for 2 h;

[0043] Antibacterial modification of electrospun fibers: Immerse the nanofiber membrane in the initiator azobisisobutyronitrile (AIBN), heat to 60 °C, and AIBN decomposes to generate free radicals. Pour 5 mL of a 3% DMC solution into the atomization cup, keep the surface of the fiber membrane 8 cm away from the atomization nozzle, perform atomization operation for 5 min. After spraying, place the fiber membrane in an oven at 80 °C for 10 min. Wash the modified nanofiber membrane three times with 50 mL of distilled water for 5 min each time, and then dry it in an oven at 80 °C for 30 min to obtain nanofiber membrane sample #3.

[0044] Example 4

[0045] Preparation of the spinning solution: Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF), continuously stir at 60 °C for 3 h until the solution is homogeneous in texture, obtaining a 10 wt% spinning solution. Add 0.5 g of methacrylic acid (MAA) to the well-stirred spinning solution and continuously stir until homogeneous;

[0046] Preparation of electrospun fibers: Load the well-stirred precursor solution into a syringe, inject it at a controllable feeding rate of 1.2 ml / h, and perform electrospinning under a high voltage of 18 kV. The rotating roller rotates at a speed of 200 r / min, keep the distance from the tip to the collector at 10 cm, perform electrospinning for 40 min, and dry it in vacuum at 25 °C for 2 hours;

[0047] Antibacterial modification of electrospun fibers: Immerse the nanofiber membrane in the initiator azobisisobutyronitrile (AIBN), heat to 60 °C, and AIBN decomposes to generate free radicals. Pour 5 mL of a 5% DMC solution into the atomization cup, keep the surface of the fiber membrane 8 cm away from the atomization nozzle, perform atomization operation for 5 min. After spraying, place the fiber membrane in an oven at 80 °C for 10 min. Wash the modified nanofiber membrane three times with 50 mL of distilled water for 5 min each time, and then dry it in an oven at 80 °C for 30 min to obtain nanofiber membrane sample #4.

[0048] Example 5

[0049] Preparation of the spinning solution: Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF), continuously stir at 60 °C for 3 h until the solution is homogeneous in texture, obtaining a 10 wt% spinning solution. Add 1 g of methacrylic acid (MAA) to the well-stirred spinning solution and continuously stir until homogeneous;

[0050] Preparation of electrospun fibers: The well-stirred precursor solution was loaded into a syringe and injected at a controlled feeding rate of 1.2 ml / h. Electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm. Electrospinning was performed for 40 min and then vacuum-dried at 25 °C for 2 hours;

[0051] Antibacterial modification of electrospun fibers: The nanofiber membrane was immersed in the initiator azobisisobutyronitrile (AIBN) and heated to 60 °C. AIBN decomposed to generate free radicals. 5 mL of the solvent without DMC was poured into the atomization cup. The surface of the fiber membrane was kept 8 cm away from the atomization nozzle, and atomization was carried out for 5 min. After spraying, the fiber membrane was placed in an oven at 80 °C for 10 min. The modified nanofiber membrane was placed in 50 mL of distilled water and washed three times, 5 min each time, and then dried in an oven at 80 °C for 30 min to obtain the nanofiber membrane sample #5.

[0052] Example 6

[0053] Preparation of spinning solution: Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF) and continuously stirred at 60 °C for 3 h until the solution was homogeneous in texture, obtaining a 10 wt% spinning solution. 1 g of methacrylic acid (MAA) was added to the well-stirred spinning solution and continuously stirred until homogeneous;

[0054] Preparation of electrospun fibers: The well-stirred precursor solution was loaded into a syringe and injected at a controlled feeding rate of 1.2 ml / h. Electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm. Electrospinning was performed for 40 min and then vacuum-dried at 25 °C for 2 hours;

[0055] Antibacterial modification of electrospun fibers: The nanofiber membrane was immersed in the initiator azobisisobutyronitrile (AIBN) and heated to 60 °C. AIBN decomposed to generate free radicals. 5 mL of a 1% DMC solution was poured into the atomization cup. The surface of the fiber membrane was kept 8 cm away from the atomization nozzle, and atomization was carried out for 5 min. After spraying, the fiber membrane was placed in an oven at 80 °C for 10 min. The modified nanofiber membrane was placed in 50 mL of distilled water and washed three times, 5 min each time, and then dried in an oven at 80 °C for 30 min to obtain the nanofiber membrane sample #6.

[0056] Example 7

[0057] Preparation of spinning solution: Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF), and continuously stirred at 60 °C for 3 h until the solution was homogeneous, obtaining a 10 wt% spinning solution. 1 g of methacrylic acid (MAA) was added to the uniformly stirred spinning solution and continuously stirred until homogeneous;

[0058] Preparation of electrospun fibers: The uniformly stirred precursor solution was loaded into a syringe and injected at a controllable feeding rate of 1.2 ml / h, and electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm. Electrospinning was carried out for 40 min and vacuum dried at 25 °C for 2 h;

[0059] Antibacterial modification of electrospun fibers: The nanofiber membrane was immersed in the initiator azobisisobutyronitrile (AIBN), heated to 60 °C, and AIBN decomposed to generate free radicals. 5 mL of a 1% DMC solution was poured into the atomizing cup, and the surface of the fiber membrane was kept 8 cm away from the atomizing nozzle for atomization operation for 5 min. After spraying, the fiber membrane was placed in an oven at 80 °C for 10 min. The modified nanofiber membrane was placed in 50 mL of distilled water and washed three times, 5 min each time, and then dried in an oven at 80 °C for 30 min to obtain the nanofiber membrane sample #7.

[0060] Example 8

[0061] Preparation of spinning solution: Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF), and continuously stirred at 60 °C for 3 h until the solution was homogeneous, obtaining a 10 wt% spinning solution. 1 g of methacrylic acid (MAA) was added to the uniformly stirred spinning solution and continuously stirred until homogeneous;

[0062] Preparation of electrospun fibers: The uniformly stirred precursor solution was loaded into a syringe and injected at a controllable feeding rate of 1.2 ml / h, and electrospinning was carried out under a high voltage of 18 kV. The rotating roller rotated at a speed of 200 r / min, and the distance from the tip to the collector was maintained at 10 cm. Electrospinning was carried out for 40 min and vacuum dried at 25 °C for 2 h;

[0063] Antibacterial modification of electrospun fibers: The nanofiber membrane was immersed in the initiator azobisisobutyronitrile (AIBN), heated to 60 °C, and AIBN decomposed to generate free radicals. 5 mL of a 1% DMC solution was poured into the atomizing cup, and the surface of the fiber membrane was kept 8 cm away from the atomizing nozzle for atomization operation for 5 min. After spraying, the fiber membrane was placed in an oven at 80 °C for 10 min. The modified nanofiber membrane was placed in 50 mL of distilled water and washed three times, 5 min each time, and then dried in an oven at 80 °C for 30 min to obtain the nanofiber membrane sample #8.

[0064] The present invention also conducts a series of performance tests on each of the obtained nanofiber membrane samples. First, it measures the filtration efficiency (a) and filtration pressure drop (b) of each nanofiber membrane sample at different test flow rates. As Figure 2-4 shown, when the air flow rate is 32 L / min, the nanofiber membrane exhibits extremely high filtration efficiency (96.54% - 99.91%). This is mainly due to the fine structure and large specific surface area of the nanofiber membrane, enabling it to more effectively capture and intercept airborne particles. As the DMC concentration increases, the filtration efficiency for particles is further improved. At this time, the pressure drop of the nanofiber membrane is between 22.7 Pa and 34.6 Pa. When the air flow rate is 65 L / min, the filtration efficiency of the nanofiber membrane decreases (92.39% - 98.63%), but the performance of the nanofiber membrane remains relatively stable, and the pressure drop fluctuates little between 77.6 Pa and 82.8 Pa, which reflects its good durability and stability. Under the condition of an air flow rate of 85 L / min, the filtration efficiency of the nanofiber membrane is between 90.44% and 96.76%, but the pressure drop increases significantly, with a minimum of 124.5 Pa and a maximum increase to 211.7 Pa.

[0065] Secondly, the present invention also tests the antibacterial rate of the nanofiber membrane samples against Escherichia coli (E. coil). E. coil culture: Use an inoculation loop to disperse the bacteria from the second-generation standard slant culture into 100 mL of liquid medium and culture it in a constant-temperature incubator at 37°C for 24 h. Dilute the activated bacterial mother liquor by 10 times and measure the OD600 value. For Escherichia coli, the OD600 is 0.5, corresponding to a bacterial solution concentration of 108 CFU / m. Gradiently dilute the bacterial mother liquor 8 times to obtain a bacterial solution concentration of 10 CFU / ml. Gradiently dilute the activated bacterial solution to 10 CFU / ml, spread it on a 9 cm TSA solid medium, invert it and place it in the incubator, and take it out after culturing in a constant-temperature incubator at 37°C for 24 h and count the number of bacterial colonies in the culture dish. As Figure 5 shown, when the mass of MAA added to the spinning solution is 0.5 g, the antibacterial rates of the fiber membranes atomized with DMC at concentrations of 0.5, 1, and 1.5 wt% are 50.9%, 73.7%, and 83.2% respectively. When the mass of MAA added to the spinning solution is 1 g, the antibacterial rates of the fiber membranes atomized with DMC at concentrations of 0.5, 1, and 1.5 wt% are 74.5%, 78.9%, and 86.3% respectively. From the above data, it can be seen that the nanofiber membranes after fog polymerization treatment all have obvious antibacterial properties.

[0066] In addition, the present invention also tests the contact angle of the nanofiber filter membrane sample. A lower contact angle indicates that the nanofiber filter membrane has better hydrophilicity, which helps the fiber membrane to absorb the water vapor generated during breathing in time and improves the wearing comfort. Figure 6 As shown in the figure, the nanofiber membrane exhibits good hydrophilicity in the air. When the mass of MAA in the spinning solution is 0.5g, the contact angle ranges from 26.5° to 49.5°. When the mass of MAA in the spinning solution is 1g, the contact angle decreases significantly, ranging from 9.7° to 21.6°, and the hydrophilicity becomes better with the increase of DMC concentration.

[0067] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a filter membrane by synergistically combining electrospinning and aerosol polymerization, characterized in that, It includes the following steps: S1. Dissolve the polymer raw material that can polymerize into fibers in N,N-dimethylformamide, stir evenly to obtain a spinning solution with a predetermined concentration, and then add a modifier and continuously stir until uniform; S2. Load the uniformly stirred precursor solution into a syringe, perform electrospinning at a set injection rate and voltage, and then vacuum dry to form a nanofiber membrane; S3. Immerse the nanofiber membrane in an initiator, heat to 60 °C to decompose the initiator to generate free radicals, pour a solvent with or without DMC into an atomization cup, keep the surface of the fiber membrane 8 cm away from the atomization nozzle for atomization, after the spraying is over, dry the fiber membrane, place the dried nanofiber membrane in distilled water for washing, and finally dry to obtain the finished nanofiber membrane.

2. The method for preparing a filter membrane based on the synergistic electrospinning-fog polymerization according to claim 1, wherein In S1, continuously stir at 60 °C for 3 h until the solution is uniform in texture to obtain a 10 wt% spinning solution, and the amount of the modifier added is 0.5 g or 1 g.

3. The method for preparing a filter membrane based on the synergistic electrospinning-fog polymerization according to claim 2, wherein In S2, inject at a controllable feeding rate of 1.2 ml / h, perform electrospinning at a high voltage of 18 kV, and the rotating roller rotates at a speed of 200 r / min, and the spinning time is 40 min.

4. A method for preparing a filter membrane based on the synergistic electrospinning-fog polymerization according to claim 3, characterized in that, The conditions for vacuum drying: vacuum dry at 25 °C for 2 hours.

5. A method for preparing a filter membrane based on the synergistic electrospinning-fog polymerization according to claim 1, characterized in that, In S3, the atomization time is 5 min. After the spraying is over, place the fiber membrane in an oven at 80 °C for 10 min. Place the dried nanofiber membrane in 50 mL of distilled water and wash it three times, 5 min each time, and then dry it in an oven at 80 °C for 30 min.

6. The method for preparing a filter membrane based on the synergistic electrospinning-fog polymerization according to claim 5, wherein, The concentration of DMC is 0.5%-5%.

7. A method for preparing a filter membrane based on the synergistic electrospinning-fog polymerization according to any one of claims 1-6, characterized in that The polymer raw material that can polymerize into fibers is one of polyacrylonitrile, polyethylene glycol or polyethylene oxide, and the modifier is selected as methacrylic acid.

8. A filter membrane prepared by the synergistic electrospinning-fog polymerization, characterized in that, It is prepared by the method described in any one of claims 1-7.

9. The filter membrane prepared by electrospinning-fog polymerization synergy according to claim 8, wherein, When the air flow rate is 32 L / min, the filtration efficiency of the filter membrane is 96.54%-99.91%, and the pressure drop is between 22.7 Pa and 34.6 Pa; When the air flow rate is 65 L / min, the filtration efficiency is 92.39%-98.63%, and the pressure drop is between 77.6 Pa and 82.8 Pa; When the air flow rate is 85 L / min, the filtration efficiency is between 90.44% and 96.76%, the minimum pressure drop is 124.5 Pa, and the maximum is 211.7 Pa.

Citation Information

Patent Citations

  • Hydrophilization modification method for polyvinyl chloride alloy ultrafiltration membrane

    CN103285743A

  • Preparation method of distillation membrane for high permeability, moisture resistance and anti-contamination membrane distillation

    CN108404685A

  • Preparation method of antibacterial anti-pollution filtering membrane

    CN112870984A

  • Efficient oil-water separation nanofiber membrane as well as preparation method and application thereof

    CN113493961A

  • A composition, a method of making a composition, and a filtration membrane

    US20240278182A1